H2 Activation in [FeFe]‐Hydrogenase Cofactor Versus Diiron Dithiolate Models: Factors Underlying the Catalytic Success of Nature and Implications for an Improved Biomimicry. Issue 5 (2nd January 2019) - Arrigoni, Federica; Bertini, Luca; Bruschi, Maurizio; Greco, Claudio; De Gioia, Luca; Zampella, Giuseppe
Abstract: Catalytic H2 oxidation has been dissected by means of DFT into the key steps common to the Fe2 unit of both the [FeFe]‐hydrogenase cofactor and selected biomimics. The aim was to elucidate the molecular details underlying the very different performances of the two systems. We found that the better enzyme performance is based on a single iron atom that is maintained electron‐poor, favoring H2 binding, although embedded within a highly electron‐rich cofactor, ensuring a facile oxidation of the Fe2 –H2 adduct. This is due to 1) CN − coordinating to both iron atoms, due to their amphipathic Lewis acid/base properties, and 2) the 4Fe4S subunit further withdrawing electrons from the Fe2 core. Preserving a moderate electron deficiency at a single iron also helps the cofactor preserve hydride affinity, which favors H2 cleavage. Such valuable characteristics allow the biocatalyst to turnover close to equilibrium conditions. All previous biomimicry has shown, in contrast, the impossibility to properly balance the two apparently contrasting aforementioned requisites, although evident progress has been made by the H2 ‐ase community. Disclosure of the differences identified could inspire the design of novel biomimics, for instance, reconsidering the use of CN − in the catalyst architecture. Indeed, in the presence of bases normally employed in oxidative catalysis, undesired stable protonation at coordinated CN −, which affects the opposite process (proton reduction), could be overcome. Abstract : Nature versus biomimicry : Dissecting H2 oxidation by the [FeFe]‐H2 ase core in comparison with a series of Fe2 S2 models has revealed that CN − ligands and the 4Fe4S subunit are the key to the higher catalytic performance of the enzyme compared with the synthetic compounds. Indeed, cyanides and cubane provide a single electron‐poor iron (which assists H2 binding) embedded within an electron‐rich environment, which in turn ensures a facile subsequent oxidation.